Traditional and new approaches to education: blended and online learning - Makoviichuk, Liliana (Kharkiv : O. M. Beketov NUUE, 2021)
The introduction of new approaches to the modern education system, namely blended and online learning, in the educational process of institution of higher education creates new opportunities for the implementation of distance learning, positively affects the work of students, their activities, motivation, consciousness, provides opportunities and conditions for transition from learning to self-education.
Keywords: blended learning, online learning, education, traditional approaches, new approaches